The effects of suspended solid on the fries of Sayan and Tengadak - Elizabeth Sinda, Tawai. (Universiti Malaysia Sarawak (UNIMAS), 2004)
This study was carried out to determine the effect of turbid water on the growth and mortality of the fries of sayan Leptobarbus hosii and tengadak Puntius schwanenfeldii. Recirculating water system was used in this study. The amount of suspended solids used was 300 mg/l. A clear water culture system was used as a control. There were eight replicate tanks for treatment and control and each tank was filled with a 34 L of water. Ten fries were placed in each of the tank. Measurements for total length, standard length, and body weight was taken once every two weeks. Mortality was recorded every day. In turbid water culture system, tengadak has a lower total length (8.5 %), standard length (12.8 %), and body weight (25.6 %) than sayan. Mortality for sayan (30 %) was higher than tengadak (21.25 %). Feed conversion ratio (FeR) is similar for sayan and tengadak in both water systems (0.30). This study shows that the effect of suspended solid differs among different species even though they are of the same life stage.